What are the limiting factors during an Ultra-Marathon?: A systematic review of the scientific literature - Hualde, G. (Universidad del Pais Vasco, 2018)
The purpose of this review is to understand what the limiting factors of the performance during Ultra-Marathons are (Ultra-Marathons and Mountain Ultra-Marathons as well). In order to clarify this issue, a systematic review of the scientific literature has been performed in the well-known PubMed database.